Public Transportation challenges in the Context of the Northwest Metropolitan Corridor of Campinas/SP - Ferreira, Denise Helena Lombardo; Santos, Rodrigo Maia; Sugahara, Cibele Roberta; Conti, Diego de Melo; Quaresma, Cristiano Capellani (Electronic Journal "Fórum Ambiental da Alta Paulista", 2025)
Objective – To analyze the effectiveness of the Northwest Metropolitan Corridor of Campinas/SP as a public policy aimed at contributing to the resolution of urban mobility issues in the Metropolitan Region of Campinas, as well as its alignment with Sustainable Development, focusing on Sustainable Development Goal 11, target 11.2. Methodology – Exploratory with a qualitative approach. Regarding technical procedures, the research is documentary with a case study strategy. Data collection was conducted through semi-structured interviews with managers of public institutions in municipalities served by the Northwest Metropolitan Corridor of Campinas/SP. Content Analysis was the technique adopted for analyzing the interviews. Originality/Relevance – The knowledge produced by this study can contribute as a subsidy for strategies and actions aimed at accessibility and urban mobility for the population of the Northwest Metropolitan Region of Campinas. Results – It was possible to identify that the integration between intermunicipal and municipal public transportation services becomes essential for the Northwest Metropolitan Corridor of Campinas/SP to reach full operation, however, integration faces challenges considering the difficulty of alignment between the actions planned by the government of the state of São Paulo and the municipalities that make up the Northwest Metropolitan Corridor of Campinas/SP. Theoretical/Methodological Contributions – Among the theoretical contributions of this study, the discussion based on scientific literature regarding the mobility and accessibility of public transportation users in the municipalities that make up the Northwest Metropolitan Corridor of Campinas/SP (CMNC). stands out. A methodological contribution enabled by the field research was the engagement through interviews with representatives from EMTU and municipal governments served by the CMNC, whose data, collected from these interviews, were analyzed using the Content Analysis technique. Social and Environmental Contributions – Urban mobility issues have worsened in recent years due to intense population growth and new individual habits. Urban mobility and accessibility are part of the range of public policies aimed at ensuring the well-being of the population.